THE EFFECT OF SUBSTITUTION AND COMBINATIONOF FEED ON THE GROWTH AND SURVIVAL RATE OF GOLD FISH LARVAE (CARASSIUS AURATUS) - Abdillah Pratama; Hamdan Alawi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The effect of substitution and combination of feed on the growth and survival rate of gold fish larvae (Carassius auratus) was conducted on May to June 2017 in the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine Sciences, University of Riau.The larvae were reared in 15 liters aquarium at stocking density 2 larvae/liter. A completely randomized design (CRD) with 5 treatments, 3 replication was used evauate the kind of feed given to the larvae. The treatment were P1 (Artemia nauplii 30 days), P2 (Artemia nauplii 10 days+Tubifex sp 10 days+Shrimp pellet 10 days), P3 (Artemia nauplii 10 days+Shrimp pellet 10 days+Tubifex sp 10 days), P4 (Tubifex sp 30 days), P5 (Shrimp pellet 30 days). Results showed that larvae fed with Tubifex sp can be substituted by Artemia nauplii as first feeding for rearing comet gold fish larvae for 30 days. The growth of fish comet larvae feed Tubifex sp significantly higher thaan those fed with shrimp pellet and artemia nauplii. The growth of comet larvae fed with Tubifex sp was 0,73 g (weight), 3,33 cm (length), 17,2 %/days (specific growth rate) 80 % (survival rate). The best combination of feeding was 10 days artemia nauplii + 10 days shrimp pellet + 10 days Tubifex sp. The water quality parameters during this research were: temperature 25-28oC, pH 5-7, dissolved oxygen 4,1-5,9 mg/l.Key words: Substitution,combination of feed, (Carassius auratus), growth, and survival